Streetwise Feminism - Hvala Tea (Amnis)
This essay interprets feminist and lesbian street actions, street art and graffiti in Ljubljana (Slovenia) as sporadic, anonymous, fleeting, and illegal interventions in the institutionalized sphere of feminist knowledge (re)production and the dominant cultural order. Selected graffiti, street art and street actions of the last fifteen years are paralleled with relevant political events and the written herstory of feminist and lesbian initiatives of the same period. The essay argues that these forms of grassroots activism, understood as one of the communication tools available to young and progressive feminists and lesbians, offer them public visibility and the possibility of creating and intermediating their own knowledge, values, and herstory – in short, an oppositional imagined community.